Reliability and validity of the Korean version of organizational justice questionnaire - Park, Hanul; Lee, Kang-Sook; Park, Yong-Jun; Lee, Dong-Joon; Lee, Hyun-Kyung (Annals of occupational and environmental medicine, 2018)
Background Many studies show that organizational justice (OJ) is related to psychological determinants of employee health. To prevent health problems related to OJ in Korean workplaces and to accurately measure OJ, we developed the Korean version of the Organizational Justice Questionnaire (K-OJQ) and assessed its validity and reliability. Methods A questionnaire draft of the K-OJQ was developed using back-translation methods, which was preliminary tested by 32 employees in Korea. Feedback was received and the K-OJQ was finalized. This study used data from 303 workers (172 males, 131 females) in Korea using the K-OJQ, job stress, and lifestyle questionnaires. Results Cronbach’s α coefficients of the internal consistency reliability was 0.92 for procedural justice and 0.94 for interactional justice. Factor analyses using SPSS 24 and Amos 23 extracted two expected factors, named procedural justice (7 items; range, 1.0–5.0) and interactional justice (6 items; range, 1.0–5.0) and showed a reliable fit (χ 2 = 182; p = .000; GFI = .912; AGFI = .877; CFI = .965; RMSEA = .077). Furthermore, higher procedural justice and interactional justice levels were correlated with lower job demand (− 0.33; − 0.36), insufficient job control (− 0.36; − 0.41), interpersonal conflict (− 0.45; − 0.51), job insecurity (− 0.33; − 0.34), organizational system (− 0.64; − 0.64), and lack of reward (− 0.55; − 0.63). Conclusions The K-OJQ was objectively validated through statistical methods.